A Single Unit Concept And Design Of A High Maneuverability Mobile Robot - Abdul Rahim, Nur Adibah (Universiti Sains Malaysia, 2018)
There are various types of high maneuverability mobile robot. One of it is spherical robot. Spherical robot utilizes an original locomotion system by displacing its center of gravity in order to generate torque and rotate itself. There are various principles developed by the researchers. Each of the principles has different designs. Moreover, the designs have its own advantages and disadvantages. Hence, in this final year project, a single unit concept and design of a high maneuverability spherical robot is developed. The spherical robot was designed using Conceptual Aided Design (CAD) software, known as SolidWorks. The selection of the design and materials done by considering the required needs or criteria. Apart from that, the programming was formed using Arduino Software. Next, to study the performance of the robot, the testing had been carried out. Pre Set Test and Free Style Test were conducted. Based on the result, the spherical robot able to move in a forward and backward direction. However, it did not able to detect and avoid obstacle well. The factors of failure are improper construction of internal chassis, positions, and interruption on ultrasonic sensor. Lastly, the future works for this project includes redesigning the internal chassis and replacing the ultrasonic sensor. Consequently, better performance of a high maneuverable spherical robot able to be obtained.